2016
DOI: 10.1163/22941932-20160120
|View full text |Cite
|
Sign up to set email alerts
|

Wood anatomy of Cupressus and its relation to geographical distribution

Abstract: The wood anatomy of 14 species of Cupressus was studied to determine whether there is a pattern of wood anatomical diversity between the species from the North and Central American (western) region and the Eurasian (eastern) region. Xanthocyparis vietnamensis and Chamaecyparis nootkatensis (syn. Xanthocyparis nootkatensis) were also studied to compare their wood anatomy, given their recent inclusion by some authors in Cupressus. The arrangement of the axial parenchyma, morphology of the transverse end walls of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…It appears that the co–occurrence of both smooth and nodular end walls of ray parenchyma can be regarded either as a special ontogenetic character related e.g ., to juvenile woods ( IAWA Committee, 2004 ); or as a character related to particular genera, e.g ., Glyptostrobus ( Visscher & Jagels, 2003 ), Fitzroya ( Gasson, Baas & Wheeler, 2011 ), Cryptomeria , Diselma , Fokienia , and Sequoiadendron ( Esteban et al, 2004 ); or even to genera of a particular region, e.g ., North American Cupressus ( Román-Jordán et al, 2016 ). Regarding the last–mentioned genus, the molecular phylogenetic analysis of Cupressus ( sensu lato) by Adams, Bartel & Price (2009) has revealed a new genus for the North American Cupressus species: Hesperocyparis Bartel & R. A.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It appears that the co–occurrence of both smooth and nodular end walls of ray parenchyma can be regarded either as a special ontogenetic character related e.g ., to juvenile woods ( IAWA Committee, 2004 ); or as a character related to particular genera, e.g ., Glyptostrobus ( Visscher & Jagels, 2003 ), Fitzroya ( Gasson, Baas & Wheeler, 2011 ), Cryptomeria , Diselma , Fokienia , and Sequoiadendron ( Esteban et al, 2004 ); or even to genera of a particular region, e.g ., North American Cupressus ( Román-Jordán et al, 2016 ). Regarding the last–mentioned genus, the molecular phylogenetic analysis of Cupressus ( sensu lato) by Adams, Bartel & Price (2009) has revealed a new genus for the North American Cupressus species: Hesperocyparis Bartel & R. A.…”
Section: Resultsmentioning
confidence: 99%
“…Additional support regarding the distinction of the western Cupressus clade from the eastern clade has been provided by xylotomical studies. Román-Jordán et al (2016) have found a link between the wood anatomical characteristics and the biogeographic distribution of Cupressaceae based on observations of specific characteristics, namely the arrangement of the axial parenchyma, transverse end walls of the axial parenchyma, presence or absence of ray tracheids, and typology of the end walls of the ray parenchyma cells and ray height. Based on their study, species with smooth, irregularly thickened, and nodular end walls of axial parenchyma are related to taxa in the North American region.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cupressus s.l. is distributed throughout the Northern hemisphere, in the Mediterranean region, in Eurasia and North and Central America [5]. Mediterranean Cupressus taxa have today a very fragmented distribution [6] as a result of both population dynamics, occurred during their long history, and human pressure [6,7].…”
Section: Introductionmentioning
confidence: 99%